Dynamically crosslinked polydimethylsiloxane-based polyurethanes with contact-killing antimicrobial properties as implantable alloplasts for urological reconstruction. (15th July 2021) - Sharma, Swati; Mandhani, Anil; Bose, Suryasarathi; Basu, Bikramjit
Abstract: A large population of patients is reported to suffer from urinary bladder-associated irreversible physiological disorders, rationalizing a continuous surge for structural and functional substitutes of urinary tissues, including ureters, bladder-wall, and urethra. The current gold standard for bladder reconstruction, an autologous gastrointestinal graft, is proven not to be an ideal substitute in the clinic. While addressing this unmet clinical need, a unique platform of antimicrobial polydimethyl siloxane-modified polyurethanes (TPU/PDMS) is designed and developed for its potential application as a urological implant. To the best of our knowledge, this study reports for the first time the successful integration of varying contents of PDMS within the molten polyurethane matrix using in situ crosslinking methodology. Thus, compatibilized binary blends possess clinically relevant viscoelastic properties to sustain high pressure, large distensions, and surgical manipulation. Furthermore, different chemical strategies are explored to covalently incorporate quaternized moieties, including 4-vinyl pyridine (4-VP), branched-polyethyleneimine (bPEI) as well as bPEI- grafted -(acrylic acid-co-vinylbenzyltriphenyl phosphonium chloride) (PAP), and counter urinary tract infections. The modified compositions, endowed with contact killing surfaces, reveal nearly three log reduction in bacterial growth in pathogenically infected artificial urine. Importantly, the antimicrobial TPU/PDMS blends support the uninhibited growth of mitochondrially viable murine fibroblasts, in a manner comparable to the medical-grade polyurethane. Collectively, the obtained results affirmed the newly developed polymers as promising biomaterials in reconstructive urology. Statement of significance: The clinical procedure for end-stage bladder disease remains replacement or augmentation of the bladder wall with a section of the patient's gastrointestinal tract. However, the absorptive and mucus-producing epithelium of intestinal segment is liable to short- and long-term complications. The dynamically crosslinked polydimethyl siloxane-based polyurethanes proposed herein, and the associated synthesis strategies to induce polycation grafted non-exhaustive contact-killing surfaces against uropathogents, have a significant clinical prospect in reconstructive urology. As an 'off-the-shelf' available alloplastic substitute, these blends offer the potential to circumvent the challenges associated with non-urinary autografts or scaffold based regenerative engineering and, thereby, shorten as well as simplify the surgical treatment. The targeted application has been conceived for a bladder patch to assist in various urinary diseases including, bladder carcinoma, refractory overactive bladder, interstitial cystitis, etc. However, given the ease of fabrication, moldability and the wide spectrum of mechanical properties that could be encompassed, these blends also present the possibility to be manifested into artificial ureteral or urethral conduits. Abstract : Graphical abstract: Image, graphical abstract